Three-dimensional Printing of Thermoplastic Materials to Create Automated Syringe Pumps with Feedback Control for Microfluidic Applications - Chen, Ming-Cheng (J Vis Exp, 2018)
Microfluidics has become a critical tool in research across the biological, chemical, and physical sciences. One important component of microfluidic experimentation is a stable fluid handling system capable of accurately providing an inlet flow rate or inlet pressure. Here, we have developed a syringe pump system capable of controlling and regulating the inlet fluid pressure delivered to a microfluidic device. This system was designed using low-cost materials and additive manufacturing principles, leveraging three-dimensional (3D) printing of thermoplastic materials and off-the-shelf components whenever possible. This system is composed of three main components: a syringe pump, a pressure transducer, and a programmable microcontroller. Within this paper, we detail a set of protocols for fabricating, assembling, and programming this syringe pump system. Furthermore, we have included representative results that demonstrate high-fidelity, feedback control of inlet pressure using this system. We expect this protocol will allow researchers to fabricate low-cost syringe pump systems, lowering the entry barrier for the use of microfluidics in biomedical, chemical, and materials research.